The Influence Of Satisfaction, Trust And Price Of Consumer Loyalty On Green Product (Case In Kandang Village Society Of Bengkulu City, Which Have Been Using Energy Saving Lighting Products) - Rina Suthia Hayu (Unib Press Universitas Bengkulu, 2014)
The increasing concern for human health and environmental sustainability, has made the companies to innovate their products into environmentally friendly products. Loyalty became the goal of marketing strategies that can be built with satisfaction, trust and price. This research aims to analyze The influence of Satisfaction, Trust and Price of Consumer Loyalty on Green Product (Case in Kandang Village Society of Bengkulu city, which have been using Energy Saving Lighting Products).The data used are primary data, sample collection method used purposive sampling with the number of respondents to 120 people, but only 102 that could be incorporated into the analysis due to lack of completeness of the respondents in its response. The analytical method used is multiple linear regression approach with the help of the program Statistical Product and Service Solutions (SPSS) version 16.0. The results of this research found partially from the calculation of the coefficients obtained by the research for satisfaction variable t provide significant value of 0.240, the trust provide significant value for 0000, prices provide significant value for 0000. Because t count on the satisfaction variable value significantly greater than 0.05, which indicates partial satisfaction variables have no effect on consumer loyalty, while for trust and price variables as significant value 0.000 <0.05, which shows in partial trust and influence consumer loyalty energy savingt lighting products. From the calculation of the F test that examines the effect of simultaneously be known F calculated for the variables of satisfaction, trust, loyalty and the price is equal to 26,750 with a significant value of 0.000 ? 0.05 then this indicates that Satisfaction, Trust, and price simultaneously have a positive effect on consumer loyalty. The conclusion of this study are the variable of satisfaction has effect on loyalty consumers, but not significant, while trust and price, have an effect on consumer loyalty.